Improving Economic Conditions Matter for Mortality: Changes in Local Economic Distress Associated with Mortality Among Medicare Fee-for-Service Beneficiaries Between 2003 and 2015 - Wallace, Harper O.; Fikri, Kenan; Weeks, Bill; Weinstein, James (Journal of General Internal Medicine, 2021)
Among Medicare fee-for-service beneficiaries, higher local economic distress is associated with less recommended care receipt;1 higher end-of-life spending among decedents;2 and higher per-capita spending, lower care quality, and higher mortality rates.3 We sought to determine whether spending and mortality rate disparities changed over time and within communities where local economic distress changed dramatically.